Crisis of corporate social responsibility and its status in Russia (Pecvnia : Revista de la Facultad de Ciencias Económicas y Empresariales, Universidad de León, 2009)
This paper picked a topic - the global financial crisis- to highlight several related problems. The current crisis was not caused by failed economic policies. The root cause is failed leadership. People sometimes forget that business ethics at its core is about excellence and high attainment rather than misdeeds and malfeasance.In recent years, however, more attention has been paid to the positive side of ethics. More managers in Russia are waking up to the ways in which positive values contribute to a company's effective day-to-day functioning, as well as its reputation and long-term sustainability.Contrary to Western Europe and Scandinavia, Corporate Social Responsibility is a relatively new concept in Central and Eastern Europe and Russia. Cultural gaps between Westerners and Locals have gradually been narrowing and becoming less divisive. Improved knowledge by foreign investors on how to operate successfully in a post-communist region, on "how to bridge the gap", greatly decreases the risk of the East-West joint venture.The views expressed in the paper are the author's own responsibility and should not be interpreted as presenting the official position paper on Corporate Governance.En este trabajo se enfoca la crisis financiera global con el fin de destacar los problemas más importantes relacionados con ésta. La presente crisis no fue provocada por causas meramente económicas. La causa fundamental radica en el liderazgo. A veces, la gente olvida que la ética de las relaciones juega un papel importante a la hora de llevar a cabo un negocio. Últimamente, no obstante, se presta más atención al aspecto positivo de la ética profesional. Un número creciente de gestores rusos emprenden el camino en el que los valores positivos conducen a un eficaz funcionamiento diario así como su prestigio y sostenibilidad a largo plazo. A diferencia de la concepción de la Europa occidental y escandinava de Responsabilidad Social Corporativa, en la Europa Central, del Este y en Rusia, es un concepto relativamente nuevo. Sin embargo, las divergencias culturales que constituían un obstáculo serio entre los inversores occidentales y locales en los últimos años se han reducido. Los inversores extranjeros van mejorando su conocimiento de como actuar con éxito en una región postcomunista. Los puentes que se han tendido entre el Este y el Oeste han reducido los riesgos de joint ventures.Las opiniones expresadas en el articulo son responsabilidad del autor y no deben interpretarse como la postura oficial rusa sobre la Gobernanza Corporativa.